Analisis Pengaruh Jumlah Puskesmas, Pengangguran Dan Indeks Pembangunan Manusia Terhadap Tingkat Kemiskinan Di Jawa Tengah Tahun 2014 - Setiyawan, Agus, Siti Fatimah Nurhayati,SE, M.Si (2016)
Poverty is a complex issue because it involves various aspects such as the fulfillment of the right to food, health, education, employment and so on. To be able to decrease poverty requires the support and cooperation of the community and the government's seriousness in addressing this issue. This study aimed to analyze the influence of the number of health centers, unemployment and human development index on poverty levels in Central Java in 2014. The analytical method used is multiple linear regression Ordinary Least Square (OLS). The data used is secondary data (cross section 2014) includes data on poverty in Central Java, the number of health centers, the unemployment rate and the human development index data. The data obtained from the Central Statistics Agency (BPS) of Central Java. The results showed that: (1) The calculation model data normality test Jarque Bera accepted at significance level α = 0.10, then the normal distribution; (2) The linearity test is also accepted at significance level α = 0.10, then shaped linear regression model; (3) The test results showed the classical assumption that there are no issues multicolinearity, no problem heterokedastisitas, and there is no problem of autocorrelation; (4) The results of t-test showed that a variable number of health centers and a significant positive effect on poverty levels. While the unemployment variable and the human development index and significant negative effect on poverty levels; (5) F test results indicate that a variable number of health centers, unemployment and human development indices have a significant effect on poverty levels; (6) R2 obtained a value of 0.497385, which means that 49.73% variable variation of poverty levels in Central Java Province can be explained by a variable number of health centers, unemployment and human development index.